Pengaruh Penggunaan Model Pembelajaran Project Based Learning terhadap Hasil Belajar Siswa pada Mata Pelajaran Fiqih - Rizki, M.; Afriani, Gusma; Zuhri, Zuhri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
In this 21st century era of globalization, students are prepared to be competent in all things, meaning they are able to face life's problems by finding creative solutions to overcome them. This study aims to test the effect of using project based learning model on students’ learning outcomes in Fiqh subject in Madrasah Tsanawiyah Negeri 2 Pekanbaru. This type of research is quantitative research with quasi-experimental research design, with nonequivalent control group design. The population in this study were all students of grade VII who took Fiqh subject in Madrasah Tsanawiyah Negeri 2 Pekanbaru, totaling 144 students. The sampling of this study used purposive sampling. The sample of this study was class VII Cendikia totaling 31 students as the experimental class and VII A totaling 29 students as the control class. Data collection techniques used observation, tests and documentation. The data analysis technique of this study used independent sample t-test. The results of the study obtained a calculated t value (2.573) > t table (1.672) with a significance level of 5%, and a significant value of 0.013 <a 0.05, then Ha is accepted and Ho is rejected. This means that there is a difference in student learning outcomes between the use of the project based learning model and the lecture method in the subject of fiqh at Madrasah Tsanawiyah Negeri 2 Pekanbaru. The Mean Score of the experimental class was 89.84 higher than the control class 85.